2012
DOI: 10.1017/s0033291712001419
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological function and suicidal behavior: attention control, memory and executive dysfunction in suicide attempt

Abstract: Background Executive dysfunction, distinct from other cognitive deficits in depression, has been associated with suicidal behavior. However, this dysfunction is not found consistently across samples. Method Medication-free subjects with DSM-IV major depressive episode (major depressive disorder and bipolar type I disorder) and a past history of suicidal behavior (n=72) were compared to medication-free depressed subjects with no history of suicidal behavior (n=80) and healthy volunteers (n=56) on a battery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
225
7
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(255 citation statements)
references
References 60 publications
22
225
7
1
Order By: Relevance
“…Thus, antidepressant drugs have an overwhelming beneficial effect on suicidality from a population perspective. This conclusion is consistent with a web of overlapping relationships between major depression, impulsivity, and other executive dysfunctions, hopelessness, and suicidality (Westheide et al, 2008;Clark et al, 2011;Carver et al, 2013;Keilp et al, 2013;Joormann and Quinn, 2014).…”
Section: Introductionsupporting
confidence: 84%
“…Thus, antidepressant drugs have an overwhelming beneficial effect on suicidality from a population perspective. This conclusion is consistent with a web of overlapping relationships between major depression, impulsivity, and other executive dysfunctions, hopelessness, and suicidality (Westheide et al, 2008;Clark et al, 2011;Carver et al, 2013;Keilp et al, 2013;Joormann and Quinn, 2014).…”
Section: Introductionsupporting
confidence: 84%
“…Prior studies using adult samples have linked suicidal behavior to specific neurocognitive factors including executive dysfunction and decision-making deficits ( Jollant et al 2005;Dour et al 2011;Chamberlain et al 2013;Keilp et al 2013) in the context of relatively unimpaired global brain functioning (Marzuk et al 2005). Behavioral and neuroimaging data have increasingly implicated prefrontal cortex (PFC) deficits, and associated reward-sensitive pathways in the expression of suicidal behavior among at-risk individuals (Mann 2003;Oquendo et al 2003;Monkul et al 2007;Jollant et al 2010;Dombrovski et al 2013).…”
mentioning
confidence: 99%
“…We have previously reported that, in an overlapping sample of older people with depression, a history of high-lethality attempts predicted poor performance on the Wisconsin Card Sort (McGirr et al, 2012). In a US study of younger adults, Keilp and colleagues (Keilp et al, 2013) found an impairment in Stroop performance in suicide attempters compared to both patient and healthy control subjects. Our finding of a high uncorrected error rate in low-lethality attempters parallels that of Brazilian study by Malloy-Diniz and colleagues (Malloy-Diniz et al, 2009) who reported a positive correlation between the number of suicide attempts and the number of errors on the Stroop test in younger bipolar I patients.…”
Section: Discussionmentioning
confidence: 96%
“…Our finding of a high uncorrected error rate in low-lethality attempters parallels that of Brazilian study by Malloy-Diniz and colleagues (Malloy-Diniz et al, 2009) who reported a positive correlation between the number of suicide attempts and the number of errors on the Stroop test in younger bipolar I patients. Findings, however, are mixed with respect to the motor component of cognitive inhibition, captured by the Go/No-Go test (Keilp et al, 2013, Raust et al, 2007, Richard-Devantoy et al, 2012. The only previous study of cognitive inhibition in elderly suicide attempters (Richard-Devantoy et al, 2012) had found significant impairments in access to relevant information and deletion of irrelevant information in comparison to both depressed and healthy control groups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation